Characterisation and use of the IRRDB germplasm in Ivory Coast and French Guyana: Status in 1997 - Clement-Demange A; Chapuset T; Legnate H; Pinard F; Seguin M (IRRDB Symposium on Natural Rubber(Hevea brasiliensis) V.1- General, Soils and Fertilization and Breeding and Selection Sessions. Ho Chi Minh City, Vietnam, 14-15 October 1997,p71-88)
An international collection was organised in Amazonia by the IRRDB in 1981 to widen the genetic base of the Hevea brasiliensis species in rubber breeding programmes. Two conservation and dispatching centres were created, one in Asia (Malaysia) and one in Africa (Ivory Coast). The present paper reports the status of research work developed by IDEFOR-DPL in cooperation with CIRAD, together with other partners (Universite Catholique de Louvain-la-Neuve in Belgium and IRAD in Cameroon) in the framework of an European-funded project. The results of the genetic diversity studies and of the agronomical assessment for yield in Ivory Coast and for resistance to Microcyclus ulei in French Guyana are described. These results permit the definition of a working population for integration into breeding programmes and a core collection for the maintainance of genetic variability over time.
Keywords: Germplasm; Hevea brasiliensis